COVID-19 in patients with heart failure: the new and the old epidemic. Issue 1145 (30th July 2020) - Sisti, Nicolò; Valente, Serafina; Mandoli, Giulia Elena; Santoro, Ciro; Sciaccaluga, Carlotta; Franchi, Federico; Cameli, Paolo; Mondillo, Sergio; Cameli, Matteo
ABSTRACT: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has spread in nearly 200 countries in less than 4 months since its first identification; accordingly, the coronavirus disease 2019 (COVID 2019) has affirmed itself as a clinical challenge. The prevalence of pre-existing cardiovascular diseases in patients with COVID19 is high and this dreadful combination dictates poor prognosis along with the higher risk of intensive care mortality. In the setting of chronic heart failure, SARS-CoV-2 can be responsible for myocardial injury and acute decompensation through various mechanisms. Given the clinical and epidemiological complexity of COVID-19, patiens with heart failure may require particular care since the viral infection has been identified, considering an adequate re-evaluation of medical therapy and a careful monitoring during ventilation.